CD20 positive T cell lymphoma: is it a real entity?. Issue 4 (26th March 2004) - Sun, T; Akalin, A; Rodacker, M; Braun, T
Abstract : CD20+ T cell lymphoma is a rare condition that includes both precursor and peripheral T cell types. However, these cases may be mistaken for T cell marker positive B cell lymphoma, thus creating diagnostic problems with subsequent clinical implications. This report describes a unique case of nodal CD20+ T cell lymphoma with simultaneous cutaneous and subcutaneous involvement. Both nodal and cutaneous lymphomas demonstrated identical monoclonal bands in the T cell receptor rearrangement assay. However, no CD20 expression was demonstrated in the skin lesion. The instability of the CD20 antigen in this tumour may imply that CD20 is not an integral part of the tumour immunophenotype and probably plays no important role in its clinical course. Techniques to avoid misdiagnosis of this lymphoma are discussed.